Typification of fifty one names in Pedicularis (Orobanchaceae) - Garg, Arti; Singh, Rajeev Kumar (Phytotaxa, 2020)
Forty five lectotypes, four second-step lectotypes and two neotypes are designated for fifty one names in Pedicularis to fix the identity and to avoid the misapplication of names. The images of the specimens of the selected lectotype and neotype at CAL are provided here being not available online.